Impairment of extra-high frequency auditory thresholds in subjects with elevated levels of fasting blood glucose - Das, Anindya; Sumit, Ahmed Faisal; Ahsan, Nazmul; Kato, Masashi; Ohgami, Nobutaka; Akhand, Anwarul Azim (Science Direct, 2022)
This article was published in the Journal of Otology [Under a Creative Commons license ] and the definite version is available at : https://doi.org/10.1016/j.joto.2017.10.003 The Journal's website is at: https://www.sciencedirect.com/science/article/pii/S1672293017300946?via%3Dihub#!